Gastronomía Tradicional, Atractivo Turístico en la Provincia Centro de Boyacá (2019)
The predominant tourist vision of gastronomy is narrow and is too often associated only with the kitchen and restaurants. This unusual vision is verified at times of a growing search for new tastes by consumers. Food is part of the heritage of the villages and when it is integrated into the tourist offer, it enhances the destination. Tourism values food and consequently the work of the actors of the gastronomic chain. Observation is then presented as a means to identify the intangible wealth of the central province of the Department of Boyacá, with the purpose of proposing a creative and innovative tourism product, which takes advantage of the wealth that exists in the region around the culinary environment. Therefore, this document presents some aspects that in our view are necessary, such as the origin of tourism research and how it serves as a basis to propose a study for the design of a tourist route of traditional gastronomy in the central province of the Department of Boyacá.